PERKEMBANGAN DAN URGENSI INSTRUMEN HUKUM ADMINISTRASI PASCA PENETAPAN UNDANG-UNDANG NOMOR 2 TAHUN 2020 PADA MASA PANDEMI COVID-19 (Institut Pemerintahan Dalam Negeri, 2021)
For more than a year, the spread of the Covid-19 virus already swept the world, including Indonesia. This study aims to determine the position of administrative law instruments in the formation of public policies, as well as to analyze the development and urgency of administrative law as an alternative to government policy during the Covid-19 pandemic. As an expectation, the results of this research may be used as a reference in analytical studies, as well as future law formation, especially the formation of laws relating to the implementation of administrative law. The research method used in this research is normative-juridical. The nature of the research used in this paper is descriptive-analytical. The results of the author's research show that administrative law instruments in the formation of public policies develop dynamically from time to time in line with the needs of the state and citizens, but the preparation of regulations that barely involve the legislature. And the absence of a bill in the National Legislation Program of 2020-2024 which reflects the existence of room for acceleration in handling Covid-19 by using government administrative legal instruments.Keywords: Legal Instruments, Administration, Covid-1